Test insertion at the RT level using functional test metrics - Harmanani, H. (2017)
A new method of redesign for testability at the Register-Transfer Level (RTL) is proposed. The method identifies hard to test parts of a an RTL design synthesized either manually or automatically using high-level synthesis tools. The design is modified by inserting additional test registers followed by a test selection process. During the selection process, two test metrics are used in order to minimize test overhead. Finally, test scheduling is performed so that to minimize the overall test time and the number of test sessions. The system outputs a VHDL description of a testable data path along with a test plan.